Effectiveness of Extracorporeal Shockwave Therapy on Controlling Spasticity in Cerebral Palsy Patients: A Meta-Analysis of Timing of Outcome Measurement - Min Cheol Chang; You Jin Choo; Sang Gyu Kwak; Kiyeun Nam; Sae Yoon Kim; Hee Jin Lee; Soyoung Kwak (MDPI AG, 2023)
Extracorporeal shockwave therapy (ESWT) has been suggested as an alternative treatment for reducing spasticity in patients with cerebral palsy (CP). However, the duration of its effect was rarely known. A meta-analysis was performed to investigate the effectiveness of ESWT at controlling spasticity in patients with CP according to the follow-up period. We included studies in which ESWT was used to manage spasticity in patients with CP, and the effect was compared with that in a control group. Finally, three studies were included. In the meta-analysis, spasticity, measured using the modified Ashworth scale (MAS), was significantly reduced after ESWT compared with that in the control group; however, it was sustained for only 1 month. After ESWT, significant increases in passive ankle range of motion (ROM) and plantar surface area in the standing position were observed compared with those in the control group and sustained for up to 3 months. Although spasticity measured using MAS was significantly reduced for only 1 month, improvement in spasticity-associated symptoms, such as ankle ROM and plantar surface area contacting the ground, persisted for over 3 months. ESWT appears to be a useful and effective therapeutic option for managing spasticity in patients with CP.